INSTITUTIONAL STRENGTHENING FOR COMMUNITY-BASED AGROTOURISM DEVELOPMENT AND ENVIRONMENTAL CONSERVATION IN JAYAWIJAYA REGENCY - Tuhuteru, Sumiyati; Rumbiak, Naftali Frans; Rumbiak, Benediktus Efer Alfaris (LPPM Univ. Ibn Khaldun Bogor, 2025)
Jayawijaya Regency holds significant potential for developing agro-tourism villages based on local wisdom and environmental conservation. However, underdeveloped community institutions remain a key barrier. This community service project aimed to strengthen village institutions through agro-tourism management training, participatory planning facilitation, and digital promotion. The participatory method was implemented over three days at Yudha Hall and organized by the Department of Culture and Tourism of Jayawijaya Regency, involving approximately 45 local tourism actors. Results indicated a significant improvement in participants' understanding of agro-tourism concepts, institutional strengthening (BUMDes and Pokdarwis), and the emergence of participatory village tourism action plans. Before the training, only 27% of participants understood basic agro-tourism concepts; this increased to 81% post-training. These achievements demonstrate that thematic training integrated with field practice is effective in building institutional capacity and advancing sustainable agro-tourism development in Jayawijaya.